Analisis Kontrastif Kala dan Aspek Bahasa Jepang dengan Bahasa Indonesia - Septa Wiki Dwi Cahyani; Vamelia Aurina Pramandhani (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research discusses the tenses and aspects in Japanese and Indonesian. The purpose of this research is to add to the learner's knowledge in understanding the tenses and aspects of Japanese and Indonesian and to help learners in applying tenses and aspects in both languages. The research method used is contrastive research, which compares the structure of Japanese and Indonesian to identify the differences between the two languages related to kala and aspect. The results show that Japanese tenses include: past tense, irregular tense, present tense, and future tense. Aspect in Japanese is characterized by morpheme changes such as -te iru and -te iku. Indonesian tenses: past tense, present tense, and future tense. Aspect in Indonesian is characterized by the prefix me- and adverbs. Contrastively, the difference in tense and aspect in the two languages lies in the markers of tense and aspect. In Japanese, it is marked by morpheme changes while in Indonesian it is marked by prefixes and adverbs. In conclusion, there are differences in the markers of tense and aspect between Japanese and Indonesian even though the meanings are the same.